A genotype VII Newcastle disease virus-like particles confer full protection with reduced virus load and decreased virus shedding. Issue 3 (14th January 2019) - Xu, Xiaohong; Ding, Zhuang; Yuan, Qianliang; Ding, Jiaxin; Li, Jindou; Wang, Weiqi; Cong, Yanlong; Ouyang, Wei; Wang, Yongshan; Qian, Jing; Yin, Renfu
Highlights: A genotype VII Newcastle disease virus-like particles was constructed. It can stimulate sufficient specific antibody response in commercial layers. It conferred full protection and provide shorter virus shedding period. Abstract: Newcastle disease (ND) is one of the most severe avian infectious disease inflicting a great loss on poultry industry worldwide. The control of ND relies on proper vaccination strategies. The vaccine strains of Newcastle disease virus (NDV) mainly belong to genotype I, II or III, which cannot fully prohibit virus shedding against the prevalent genotype VII virulent strain attack. To develop a safe, genotype matched vaccine candidate, we employed a bac-to-bac expression system and constructed a genotype VII NDV strain based virus-like particles (NDV VLPs). It was constructed with NDV M protein as the skeleton, and protective antigen F and HN proteins displayed on the surface. The NDV VLPs exhibited a similar appearance to the live NDV particles, but with denser F and HN proteins displayed on the surface. The immunization assay indicated that NDV VLPs stimulated a longer protection period, less tissue virus loading and shorter virus shedding period than the commercialized LaSota-formulated vaccine when challenged with genotype VII NDV strain. These results proposed the potential role of NDV VLPs as an alternative to current live genotype unmatched vaccine for the control and eliminate NDV in the avian flocks.